Practical role of oil palm fronds in Malaysia’s sustainable palm oil industry - Zakaria, Mohd Rafein; Ahmad Farid, Mohammed Abdillah; Hafid, Halimatun Saadiah; Andou, Yoshito; Hassan, Mohd Ali (Elsevier, 2024)
In the pursuit of sustainability, oil palm frond (OPF) is emerging as an important renewable resource in Malaysia’s thriving palm oil industry, presenting both opportunities and challenges. This review presents an in- depth assessment of the current landscape of the Malaysian palm oil industry, emphasizing the abundance of OPF, logistical difficulties, and current and future potential industrial uses. Amidst the industry’s phenomenal expansion, the generation of OPF was estimated at 59.3 and 156.5 million tonnes in 2023 from Malaysia and Indonesia, respectively. Implementing existing and new policies can fully capitalize on the socioeconomic and ecological benefits of integrating OPF into the palm oil supply chain. This offers several advantages, including economic growth, environmental and sustainability practices, resource optimization, support for innovation and commercialization, energy diversification, and investment attraction. The future of OPF utilization in Malaysia lies in developing more valuable applications and improving integrated biomass techniques. Emerging technologies like enzymatic hydrolysis, lignocellulosic fractionation, biosugars, bioethanol, ruminant feed, and biochar production offer great potential to unlock OPF’s full benefits. However, technological hurdles and limited industrial implementation continue to hamper the widespread adoption of these innovative solutions. Future research for enhancing the efficiency of conversion processes, evaluating the economic viability of OPF- based products, and investigating the environmental impacts of OPF valorization would be crucial in unlocking the full potential of this abundant and promising biomass resource.